Differentiation and characterization of osteoclasts from human induced pluripotent stem cells - Blümke, Alexander Felix; Simon, Jessica; Leber, Elizabeth; Scatena, Marta; Giachelli, Cecilia M. (Developmental biology, 2024)
Watch this Scientific Journal Video about Differentiation and Characterization of Osteoclasts from Human Induced Pluripotent Stem Cells at JoVE.com